CAR-T cell immunotherapy for ovarian cancer: hushing the silent killer - Nasiri, Fatemeh; Farrokhi, Khadijeh; Safarzadeh Kozani, Pouya; Mahboubi Kancha, Maral; Dashti Shokoohi, Setareh; Safarzadeh Kozani, Pooria (Frontiers in Immunology, 2023)
As the most lethal gynecologic oncological indication, carcinoma of the ovary has been ranked as the 5th cause of cancer-related mortality in women, with a high percentage of the patients being diagnosed at late stages of the disease and a five-year survival of ~ 30%. Ovarian cancer patients conventionally undergo surgery for tumor removal followed by platinum- or taxane-based chemotherapy; however, a high percentage of patients experience tumor relapse. Cancer immunotherapy has been regarded as a silver lining in the treatment of patients with various immunological or oncological indications; however, mirvetuximab soravtansine (a folate receptor α-specific mAb) and bevacizumab (a VEGF-A-specific mAb) are the only immunotherapeutics approved for the treatment of ovarian cancer patients. Chimeric antigen receptor T-cell (CAR-T) therapy has achieved tremendous clinical success in the treatment of patients with certain B-cell lymphomas and leukemias, as well as multiple myeloma. In the context of solid tumors, CAR-T therapies face serious obstacles that limit their therapeutic benefit. Such hindrances include the immunosuppressive nature of solid tumors, impaired tumor infiltration, lack of qualified tumor-associated antigens, and compromised stimulation and persistence of CAR-Ts following administration. Over the past years, researchers have made arduous attempts to apply CAR-T therapy to ovarian cancer. In this review, we outline the principles of CAR-T therapy and then highlight its limitations in the context of solid tumors. Ultimately, we focus on preclinical and clinical findings achieved in CAR-T-mediated targeting of different ovarian cancer-associated target antigens.